Violence against women and girls in the Caribbean: an intervention and lessons learned from Jamaica - Muturi, Nancy W. (My University, 2010)
This paper describes the interagency campaign implemented in 1998 that specifically addressed violence against women and girls, documenting the lessons learnt and key findings of the intervention as well as some implications. The terms ‘violence against women (and girls)’ and ‘gender-based violence’ are used synonymously in this paper as in many writings on gender issues. We define gender-based violence as violence based on one’s gender, which is characterized by imbalanced gender relations. Gender is a social construct ascribing feminine or masculine identity and roles to biologically determined female and male persons (Kesselman et al, 1999; Young in Mahammad and Shepherd, 1999). The power imbalance in gender relations is most evident where men and boys are attributed socially higher value than women and girls. Gender-based violence appears mostly as violence against women and girls perpetuated by men and boys, where the “aggressor is often motivated by gender considerations such as the need to reinforce male power and privilege” (Rico, 1997:8). The first section of the paper addresses the theoretical perspectives positing an explanation for the occurrence of gender-based violence. The next section describes the extent of the gender-based violence problem in the Jamaican context through an overview of some cases of violence against women and girls that received media attention. The main body of the paper focuses on the campaign, describing the methods used to gather information as well as the campaign process and challenges. It concludes with the lessons learned and key findings from which future interventions might benefit.
Keywords: Violence; Women; HIV; AIDS; Jamaica; Caribbean